Lesões por causas externas em clube recreativo - Caixeta, Adriana (2005)
Physical activity and sports practice have been associated with a healthy life, but they can also cause injuries. The aim of this work is to study the epidemiology and classify the most frequent lesions from external causes in a country club in Uberlândia, Minas Gerais State. We prospectively obtained data from 885 patients with injuries from external causes attended at the medical department of this country club, in 2004. Statistical analysis was performed using chi-square and Fisher s exact tests (p<0.01). We observed more injuries among males, with ages of 10 to 19 years. The lesions occurred more frequently during sports practice indoors. Fall was the main cause of injuries, above all in age limits. More than 50% of the lesions in almost half of the patients, resulting from running and walking, occurred in the lower limbs. Sprains, strains, and contusions were the most frequent injuries, while fractures and dislocations affected less than 5% of the patients. Among children, we observed more contusions and skin abrasions and less strains/sprains compared to teenagers and adults. Sprains, strains, fractures, and dislocations were the main reasons for a more complex medical assistance outside the country club. Local cooling with ice packs was the most frequent treatment used. We concluded that injuries affected more frequently males with ages of 10 to 19 years, mainly during sports practice indoors; fall was the most frequent cause of lesions, above all in age limits; strains/sprains and contusions were the most frequent lesions; the lower limb was the most affected region; local cooling was the most common treatment used; strains/sprains, fractures and dislocations were the main reasons for a more complex treatment outside the country club.